Stevia rebaudiana: Phytochemical, pharmacological activities, and plant tissue culture (a mini-review) - FAHRAUK FARAMAYUDA; RENALDI OKTAVIANUS; ELFAHMI ELFAHMI (Jurnal Natural, 2022)
Stevia rebaudiana is very famous as natural sweeteners and potentially for lowering blood sugar. The benefits of Stevia rebaudiana are numerous, and various pharmacological activities have been found, such as efforts to treat diseases such as diabetes, obesity, dental caries, hypoglycemia, and hypertension. The main sweet compounds in Stevia rebaudiana are rebaudioside A and stevioside, especially in the leaves. This review examines aspects of phytochemistry, pharmacological activity, micropropagation, and in-vitro culture modification of Stevia rebaudiana plants. Online and offline literature searches were conducted to compile the articles. PubMed (Medline), Web of Science, is used to retrieve online publications using the following search terms: Stevia rebaudiana, stevia herbs, traditional medicine, pharmacological activities, toxicity, secondary metabolite content, phytochemicals, and plant tissue culture of Stevia rebaudiana . This review is also a compilation of four previous reviews and is accompanied by the latest data from research journals on Stevia rebaudiana.